Automatic Excitation Control Using PI Method Based on Analysis Root Locus for Synchronous Generator - Ravi, Alwy Muhammad; Nugraha, Anggara Trisna (Universitas Negeri Malang, 2023)
The demand for electrical energy is increasing (at 2–3 percent per year). It is necessary to utilize the energy available in nature optimally and stably to fulfill electricity needs. Synchronous generators have an essential role in fulfilling electricity needs. Maintaining and improving the operational stability of the synchronous generator is fundamental to the safe and economical operation of an electric power system. The use of control methods to increase control excitation is recognized as an economical and effective way. Previous research shows there are still areas for improvement in the excitation control method. Thus, this research focuses on optimizing the automatic excitation system using the PI control method with stability analysis using the root locus. The effect of PI control on the results of the characteristics response has Tr is 1.9 s, Ts is 6.6 s, Mp is 38.95 percent, and Ess is 11.02 percent. While the generator excitation current will increase in line with the increase in load current, and the resulting output voltage will be stable with errors that occur when compared to the nominal voltage is 10.51 percent because the sensor reading is affected by a frequency that is not following the operating frequency.DOI: 10.17977/um024v8i12023p036